Space, infrastructure and budgets : a case of roads and stormwater maintenance in the City of Ekurhuleni, South Africa 2000-2020 - Murray, Noëleen (University of Pretoria, 2025)
Thesis (PhD (Development Studies))--University of Pretoria, 2025.